Deep Temporal Nerve Transfer for Facial Reanimation: Anatomic Dissections and Surgical Case Report. Issue 1 (8th July 2018) - Mahan, Mark A; Sivakumar, Walavan; Weingarten, David; Brown, Justin M
Abstract: BACKGROUND: Facial nerve palsy is a disabling condition that may arise from a variety of injuries or insults and may occur at any point along the nerve or its intracerebral origin. OBJECTIVE: To examine the use of the deep temporal branches of the motor division of the trigeminal nerve for neural reconstruction of the temporal branches of the facial nerve for restoration of active blink and periorbital facial expression. METHODS: Formalin-fixed human cadaver hemifaces were dissected to identify landmarks for the deep temporal branches and the tension-free coaptation lengths. This technique was then utilized in 1 patient with a history of facial palsy due to a brainstem cavernoma. RESULTS: Sixteen hemifaces were dissected. The middle deep temporal nerve could be consistently identified on the deep side of the temporalis, within 9 to 12 mm posterior to the jugal point of the zygoma. From a lateral approach through the temporalis, the middle deep temporal nerve could be directly coapted to facial temporal branches in all specimens. Our patient has recovered active and independent upper facial muscle contraction, providing the first case report of a distinct distal nerve transfer for upper facial function. CONCLUSION: The middle deep temporal branches can be readily identified and utilized for facial reanimation. This technique provided a successful reanimation of upper facial muscles with independent activation. Utilizing multiple sources for neurotization of the facial muscles, different potions of the face can be selectively reanimated to reduce the risk of synkinesis and improved control.